(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
Songs are an integral part of almost if not all societies around the world. The primary function of songs is entertainment; however, they perform other functions as well such as to provide an understanding of the daily lives of the people, to express personal views and opinions, to transmit societal and cultural norms and beliefs, to subvert and question the status quo and so forth. This paper analyses a song entitled Magosi (Tlhatswa Lesire) thematically to find out what issues are being communicated. The argument of this paper is that the artist uses this verbal art form to critique and ridicule the Setswana societal and cultural expectations. It concludes that songs are a medium through which Batswana women can challenge and subvert the inequality and patriarchal ideology prevalent in their societies.